2007
DOI: 10.1194/jlr.m700086-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amino acid substitutions at glycine 420 on SR-BI cholesterol transport function

Abstract: Scavenger receptor class B type I (SR-BI) facilitates the uptake of HDL cholesteryl esters (CEs) in a twostep process involving binding of HDL to its extracellular domain and transfer of HDL core CEs to a metabolically active membrane pool, where they are subsequently hydrolyzed by a neutral CE hydrolase. Recently, we characterized a mutant, G420H, which replaced glycine 420 in the extracellular domain of SR-BI with a histidine residue and had a profound effect on SR-BI function. The G420H mutant receptor exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…We examined the functional importance of each individual leucine within this motif of SR-BI, and used NMR analysis to further understand why several single leucine mutations lead to disruption of different receptor functions. We observed that mutation of L413 significantly disrupts HDL binding, HDL-CE uptake, and cholestenone production and corroborates previous findings (Parathath et al, 2007; Parathath et al, 2004; Sahoo et al, 2007b) that residues in this region are imperative for all of these cholesterol transport functions. Indeed, we recently showed that mutation of tryptophan 415 to phenylalanine disrupted several SR-BI functions (Holme et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…We examined the functional importance of each individual leucine within this motif of SR-BI, and used NMR analysis to further understand why several single leucine mutations lead to disruption of different receptor functions. We observed that mutation of L413 significantly disrupts HDL binding, HDL-CE uptake, and cholestenone production and corroborates previous findings (Parathath et al, 2007; Parathath et al, 2004; Sahoo et al, 2007b) that residues in this region are imperative for all of these cholesterol transport functions. Indeed, we recently showed that mutation of tryptophan 415 to phenylalanine disrupted several SR-BI functions (Holme et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that the levels of selective uptake efficiency were artificially high as a result of the low amount of HDL binding. This trend has been observed in a previous study 38 . It is also possible that mutation of Trp 415 to Phe results in a conformational change within the receptor that makes it less favorable for HDL binding.…”
Section: Discussionsupporting
confidence: 90%
“…The C251S, C323S, C384S, and Cys-less mutant receptors were produced and sequenced by TOP Gene Technologies (Pointe-Claire, Quebec, Canada). Myc-SR-BI (36) and G420C-SR-BI (40) were previously described.…”
Section: Methodsmentioning
confidence: 99%